Web resources scientific libraries of medical universities in Ukraine: a comparative analysis (Journal of EAHIL, 2015)
Seventeen Ukrainian medical university libraries websites were analysed. Web resources of these libraries can be divided according to the type and character of resources into the 3 categories: own libraries web resources, library website as part of a university website, single page with information about the library on the university website.The information for library users is most fully presented on individual sites of libraries. Content management systems are generally used to create sites. Most of the web resources of the Ukrainian scientific university libraries require a periodical updating of their resources, availability of on-line information and services.